2009
DOI: 10.1007/s00347-009-1934-0
|View full text |Cite
|
Sign up to set email alerts
|

Topische antiangiogene Therapie an der Hornhaut

Abstract: Avastin and GS101 eye drops are the first specific angiogenesis inhibitors for topical inhibition of corneal angiogenesis available for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…While this more targeted treatment avoids the side-effects of steroids, experimental and clinical studies have shown only a limited reduction in corneal neovessels. Using locally-applied anti-VEGF by topical 197 , subconjunctival 219 , intrastromal 220 , or intraocular route 221 , neovessel reduction in the range of 15-20 % in experimental studies 222 and of 36-61% in clinical studies 197,219,223 has been reported. Anti-VEGF may also have a shorter therapeutic window compared to steroids 159 .…”
Section: Anti-vegf Treatmentmentioning
confidence: 99%
“…While this more targeted treatment avoids the side-effects of steroids, experimental and clinical studies have shown only a limited reduction in corneal neovessels. Using locally-applied anti-VEGF by topical 197 , subconjunctival 219 , intrastromal 220 , or intraocular route 221 , neovessel reduction in the range of 15-20 % in experimental studies 222 and of 36-61% in clinical studies 197,219,223 has been reported. Anti-VEGF may also have a shorter therapeutic window compared to steroids 159 .…”
Section: Anti-vegf Treatmentmentioning
confidence: 99%
“…Vascular endothelial growth factor (VEGF) is thought to be one of the key mediators in the process of NV, and the effects of anti-VEGF antibodies have been demonstrated on various experimental corneal NV models (for review see Gupta and Illingworth 2011). So far, anti-VEGF antibodies have been licensed exclusively for vitreoretinal diseases, but they are off-label for corneal NV, as there is little evidence for their efficacy on the cornea (Regenfuss et al 2009; Benayoun et al 2012). …”
Section: Introductionmentioning
confidence: 99%